Infection with Toxoplasma gondii in a red kangaroo (Macropus rufus) and a Patagonian mara (Dolichotis patagonum) in captivity - Nataly Díaz-Ayala (Revista Brasileira de Parasitologia Veterinária)
Abstract Toxoplasmosis is an infectious, zoonotic and parasitic disease, caused by Toxoplasma gondii. In this manucript, two cases of infection with T. gondii in captive animals from a zoological park in the central region of Chile are described. One case was a red kangaroo (Macropus rufus), which is highly susceptible to the infection, and the other was a Patagonian mara (Dolichotis patagonum), a rodent in which there is no previous report of the infection. Both animals had myocarditis, with the presence of intralesional tachizoites and cysts suggestive of infection with T. gondii. This infection was confirmed by immunohistochemistry in both animals. The origin of the infection is unknown, but it is likely that free ranging domestic felines were associated with the dissemination of the parasites. This highlights the importance of controlling the domestic animal populations in zoological parks. To the best of our knowledge, this is the first time that T. gondii infection is described in a Patagonian mara, adding a new host for this infectious agent.